The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/land10070761
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Natural Areas on Post-Mining Brownfields as an Opportunity to Strengthen the Attractiveness of a Small Town. An Example of Radzionków in Southern Poland

Abstract: The socio-economic and political changes of the end of the 20th century in Central and Eastern Europe had significant impacts on the transformation of urban spaces, especially in industrial and mining towns. The article attempts to explain the essence of these changes concerning the spatial development of—a small post-mining town in southern Poland. This article evaluates urban development policy in response to the significant land-use changes in the small post-mining city of Radzionków, with particular attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
4
0
3
Order By: Relevance
“…Deşi se pune accentul pe dezvoltarea durabilă şi utilizarea raţională a resurselor, există încă numeroase areale post-miniere care nu sunt utilizate adecvat (Belzyt, 2019). Astfel sa impus ideea de revitalizare a acestor zone, prin măsuri ca: integrarea în circuitul turistic (Cercleux et al, 2018;Lamparska, 2019;Kaźmierczak et al, 2019); ecologizarea şi transformarea în parcuri sau grădini botanice (Marot and Harfst, 2021;Kantor-Pietraga et al, 2021) sau amenajarea unor parcuri industriale (Krzysztofik et al, 2020). În acest context, studiul prezent abordează fosta zonă minieră Ghelari în vederea revitalizării acesteia şi includerii clădirilor industriale în circuitul funcţional.…”
Section: Contextul Teoreticunclassified
“…Deşi se pune accentul pe dezvoltarea durabilă şi utilizarea raţională a resurselor, există încă numeroase areale post-miniere care nu sunt utilizate adecvat (Belzyt, 2019). Astfel sa impus ideea de revitalizare a acestor zone, prin măsuri ca: integrarea în circuitul turistic (Cercleux et al, 2018;Lamparska, 2019;Kaźmierczak et al, 2019); ecologizarea şi transformarea în parcuri sau grădini botanice (Marot and Harfst, 2021;Kantor-Pietraga et al, 2021) sau amenajarea unor parcuri industriale (Krzysztofik et al, 2020). În acest context, studiul prezent abordează fosta zonă minieră Ghelari în vederea revitalizării acesteia şi includerii clădirilor industriale în circuitul funcţional.…”
Section: Contextul Teoreticunclassified
“…Industrial heritage is probably the most commonly identified asset in industrial towns. These are tangible remnants of older industrial production, such as industrial sites, buildings and landscapes, which are commonly converted for tourism use (Bosák et al, 2018) or other forms of brownfield development (Kantor-Pietraga et al, 2021;Marot and Harfst, 2021). However, Görmar and Harfst (2019) caution that this may be too narrow an understanding of what industrial culture can offer, and that intangible aspects are even more important for new path development.…”
Section: Sociocultural Assetsmentioning
confidence: 99%
“…W krajobrazie powiatu znajduje się wiele nieczynnych kamieniołomów wapienia i dolomitów, np. nieeksploatowany kamieniołom na zboczu Księżej Góry w Radzionkowie (Kantor-Pietraga, Zdyrko, Bednarczyk, 2021). W centralnej części powiatu występują utwory jurajskie, takie jak: piaski, muły i piaskowce wapieni dolnej, środkowej i górnej jury.…”
Section: Historia Tradycji Przemysłowych W Powiecie Tarnogórskimunclassified
“…W jej przypadku również zaplanowane nowe inwestycje na terenach poprzemysłowych w większości są zrealizowane. Plany te nie dotyczą terenu w Radzionkowie (Kantor-Pietraga, Zdyrko, Bednarczyk, 2021). Z kolei kamieniołomy znajdujące się na terenie Radzionkowa są miejscami zagospodarowanymi turystycznie.…”
Section: Zagospodarowanie Terenów Poprzemysłowych W Powiecie Tarnogór...unclassified